Burnout syndrome among healthcare personnel during the COVID-19 pandemic, Veracruz, Mexico - Rosales-Saade, Andrés (2025)
Objective: To determine the prevalence of burnout syndrome and its associated factors amongnursing staff, physicians and resident physicians during the COVID-19 pandemic in a tertiary hospitalrepurposed for COVID-19 patient care. Materials and methods: A quantitative, cross-sectional andanalytical study was conducted using the Maslach Burnout Inventory (MBI) and a self-developedquestionnaire to evaluate sociodemographic, occupational and pandemic-related variables. Thestudy included 225 healthcare professionals: 93 nurses, 60 physicians and 72 resident physiciansworking in general surgery, internal medicine, obstetrics and gynecology, emergency, intensivecare unit (ICU), pediatrics and epidemiology services across morning, afternoon, evening and night shifts and compressed workweeks in a tertiary hospital in Veracruz, Mexico, which was converted into a COVID-19-designated hospital during the pandemic. Results: The overall prevalence of burnout syndrome was 58.7 %. Resident physicians were the most affected group (77.8 %), followed by physicians (55 %) and nursing staff (45 %). Among the dimensions of burnout syndrome, high emotional exhaustion was observed in 38.2 % of workers, high depersonalization in 31.1 % and low personal accomplishment in 36 %. The variables most strongly associated with burnout syndrome were the number of children, age, years of employment at the center, profession, weekly working hours, job position, type of contract and shift. Conclusions: The findings suggest that the excessive weekly working hours and the heavy workload assigned to resident physicians may significantly contribute to the high prevalence of burnout syndrome, as this group was the most severely affected.